2018
DOI: 10.1371/journal.pone.0199622
|View full text |Cite
|
Sign up to set email alerts
|

Altered circadian genes expression in breast cancer tissue according to the clinical characteristics

Abstract: Breast cancer has a multifactorial etiology. One of the supposed and novel mechanisms is an alteration of circadian gene expression. Circadian genes play a crucial role in many physiological processes. These processes, such as genomic stability, DNA repair mechanism and apoptosis, are frequently disrupted in breast tumors. To assess the significance of circadian gene expression in breast cancer, we carried out an analysis of CLOCK, BMAL1, NPAS2, PER1, PER2, PER3 and CRY1, CRY2, TIMELESS, CSNK1E expression by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 36 publications
4
31
0
3
Order By: Relevance
“…Similarly, CpG methylation of the PER1, PER2 and PER3 promoters was found to correlate with changes in protein expression in 50% of breast tumours compared to normal tissue originating from the same patients (Chen et al 2005), PER1, PER2, PER3, CRY2 expression was found to be significantly downregulated, while CLOCK expression was upregulated in breast tumour samples compared to the non-tumour samples. CRY2 and NPAS2 were also downregulated in the poorly differentiated breast cancer in comparison with well and moderately differentiated ones suggesting a possible prognostic role in breast cancer (Lesicka et al 2018).…”
Section: Clock Genes and Cancermentioning
confidence: 94%
“…Similarly, CpG methylation of the PER1, PER2 and PER3 promoters was found to correlate with changes in protein expression in 50% of breast tumours compared to normal tissue originating from the same patients (Chen et al 2005), PER1, PER2, PER3, CRY2 expression was found to be significantly downregulated, while CLOCK expression was upregulated in breast tumour samples compared to the non-tumour samples. CRY2 and NPAS2 were also downregulated in the poorly differentiated breast cancer in comparison with well and moderately differentiated ones suggesting a possible prognostic role in breast cancer (Lesicka et al 2018).…”
Section: Clock Genes and Cancermentioning
confidence: 94%
“…Seven core clock genes including CLOCK, BMAL1, PER1, PER2, PER3, CRY1, CRY2 were shown to be downregulated in colorectal liver metastases and lower mRNA levels of PER3 were associated with the increased number of metastases [4]. The altered mRNA levels of several circadian genes were reported in breast tumor samples compared to the non-tumor samples; while CLOCK and TIMELESS genes were upregulated, PER1, PER2, PER3, and CRY2 were downregulated [18]. In a very recent study, significantly low mRNA expression levels of Per1, Per2, and Per3 were reported in locally advanced head and neck squamous cell carcinoma compared with early-stage cancer patients [6].…”
Section: Resultsmentioning
confidence: 94%
“…Epidemiological studies have linked circadian clock disruption through night shift work or light-at-night exposure with hormone-dependent cancers, and this evidence has been recently reviewed [2]. Additionally, clinical evidence connects methylation of clock gene promoters or single nucleotide polymorphisms (SNPs) with multiple cancer types, including breast [20,21], prostate [22,23], lung [24], colorectal [25,26], HCC [27] and other tumor types. To understand the global changes in core clock genes or CCGs, recent bioinformatics approaches have compared patient data from The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), Genomics of Drug Sensitivity in Cancer (GDSC), and the Cancer Therapeutics Response Portal (CTRP).…”
Section: Clinical Evidence Linking the Clock With Cancermentioning
confidence: 99%